2018
DOI: 10.1080/09168451.2018.1517592
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise oral immunotherapy for 10 days in an egg-white allergy mouse model did not ameliorate the severity of allergy but induced the production of allergen-specific IgA

Abstract: We examined whether the stepwise oral immunotherapy (OIT) for 10 days ameliorates the severity of allergy and the biomarkers in an allergy mouse model. The OIT could not protect anaphylaxis symptoms after allergen challenges but promote the production of antibodies, especially allergen-specific IgA. It was suggested that this OIT influenced the function of immuno response against the allergen. Abbreviations: EW: egg white; IFC: intraperitoneal food challenge; IFN-γ: interferon-γ; IL: interleukin; OVA: ovalbumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…We initially found marked increases in allergen-specific IgA in a trial of OIT for peanut an observation that has subsequently been extended by others to cow’s milk and egg OIT ( 14 , 32 35 ). Murine models have also documented specific IgA responses following food allergen ingestion and OIT ( 24 , 36 38 ). Despite the consistent observation of association between IgA responses and food tolerance in humans and in murine models of food allergy, neither the direct contributions of IgA to tolerance nor the mechanisms thereof have been established.…”
Section: Discussionmentioning
confidence: 99%
“…We initially found marked increases in allergen-specific IgA in a trial of OIT for peanut an observation that has subsequently been extended by others to cow’s milk and egg OIT ( 14 , 32 35 ). Murine models have also documented specific IgA responses following food allergen ingestion and OIT ( 24 , 36 38 ). Despite the consistent observation of association between IgA responses and food tolerance in humans and in murine models of food allergy, neither the direct contributions of IgA to tolerance nor the mechanisms thereof have been established.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Over the past few years, different groups demonstrated that induction of other antibody isotypes, such as IgA, IgG 1 , IgG 4 , and IgD, can ameliorate IgE-mediated reactions. 15,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Specifically, several clinical trials of egg oral immunotherapy reported increases of serum antigen-specific IgA, IgG 1 , and IgG 4 in patients that responded to treatment. 32,33 Interestingly, the ability of the antibodies to block IgE-mediated responses could be largely dependent on their antigen specificity rather than isotype.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, different groups demonstrated that induction of other antibody isotypes, such as IgA, IgG 1 , IgG 4 , and IgD, can ameliorate IgE‐mediated reactions 15,25‐40 . Specifically, several clinical trials of egg oral immunotherapy reported increases of serum antigen‐specific IgA, IgG 1 , and IgG 4 in patients that responded to treatment 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…In an allergic mouse model, animals sensitized with egg white have given information about IgA in AIT. After 12 days of administration, allergen-specific IgA levels were higher in OIT mouse with short-term treatment [77]. A recent human OIT study has reported that during egg OIT, egg-and component-specific IgA, IgA1 and IgA2 levels in plasma also increased in patients who responded to therapy.…”
Section: Relationship Among the Responses Of Ige Igg And Igamentioning
confidence: 92%